Metabolic niches in the rhizosphere microbiome: new tools and approaches to analyse metabolic mechanisms of plant–microbe nutrient exchange. (20th December 2018) - Jacoby, Richard P; Kopriva, Stanislav
Abstract : We review new tools and approaches for dissecting how metabolism shapes the root microbiome, in which rhizosphere microbes consume plant metabolites as growth substrates and different strains occupy discrete metabolic niches. Abstract: Plants nourish rhizospheric microbes via provision of carbon substrates, and the composition of the microbiome is strongly influenced by metabolic phenomena such as niche differentiation, competitive exclusion, and cross-feeding. Despite intensive investigations of the taxonomic structure in root microbiomes, there is relatively little biochemical knowledge of the metabolic niches occupied by microbial strains in the rhizosphere. Here, we review new tools and approaches that are boosting our knowledge of the metabolic mechanisms that shape the composition of the root microbiome. New studies have elucidated biochemical pathways that mediate root colonisation and pathogen suppression, and synthetic communities are emerging as a powerful tool to understand microbe–microbe interactions. Knowledge of root exudate composition is being advanced by new metabolomics methodologies, which have highlighted that specific exudate components can inhibit pathogen growth, and that certain metabolites can recruit mutualistic strains according to substrate uptake preferences. Microbial genomics is rapidly advancing, with large collections of isolated rhizosphere strains and mutant libraries giving new insights into the metabolic mechanisms of root colonisation. Exometabolomics is emerging as a powerful methodology for directly observing microbial uptake of root metabolites, and also for profiling microbial cross-feeding. Integrative studies using these resources should enable rapid advances, particularly when applied to standardised experimental set-ups and model synthetic communities.